1994
DOI: 10.1002/jmv.1890430207
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity titration of a prototype strain of hepatitis E virus in cynomolgus monkeys

Abstract: The infectivity titer of a standard stock of the SAR-55 strain of hepatitis E virus (HEV) was determined in cynomolgus macaques (Macaca fascicularis) and the effect of dose on the course of the infection was examined by weekly monitoring of alanine aminotransferase (ALT) and anti-HEV levels. Antibody to HEV (anti-HEV) was measured with ELISAs based on ORF-2 recombinant antigens consisting of either a 55 kDa region expressed in insect cells or shorter regions expressed as fusion proteins in bacteria. The ELISA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
0
8

Year Published

1996
1996
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 128 publications
(103 citation statements)
references
References 25 publications
6
89
0
8
Order By: Relevance
“…One rhesus monkey seroconverted at 5 weeks postinoculation and the other at 8 weeks. The time to seroconversion in these two transfected rhesus monkeys was similar to those observed previously when the Sar-55 virus in a clinical sample was titrated in cynomolgus macaques, a species used interchangeably with rhesus macaques for HEV studies (16). The titration study demonstrated that time to seroconversion increased as the dose of virus was decreased, but the severity of hepatitis generally decreased as the dose was decreased.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One rhesus monkey seroconverted at 5 weeks postinoculation and the other at 8 weeks. The time to seroconversion in these two transfected rhesus monkeys was similar to those observed previously when the Sar-55 virus in a clinical sample was titrated in cynomolgus macaques, a species used interchangeably with rhesus macaques for HEV studies (16). The titration study demonstrated that time to seroconversion increased as the dose of virus was decreased, but the severity of hepatitis generally decreased as the dose was decreased.…”
Section: Discussionsupporting
confidence: 82%
“…Animals infected with HEV can develop hepatitis, as demonstrated by elevation of serum liver enzymes and appearance of histopathological changes in the liver. The severity of the hepatitis appears to depend on the initial viral load, and a low dose of virus can infect without causing overt disease (16). Viremia does occur, and virus can be detected also in bile and feces.…”
Section: H Epatitis E Virus (Hev) Is An Unclassified Nonenvelopedmentioning
confidence: 99%
“…The appearance of viremia and shedding of virus in feces is apparently dose dependent, as virus shedding in blood and feces appeared earlier in chickens inoculated with a higher dose than in those inoculated with a lower dose. This observation is consistent with those from the infectivity titration results in experiments with monkeys inoculated with human HEV (32).…”
Section: Discussionsupporting
confidence: 91%
“…Cynomolgus monkeys infected by intravenous inoculation of HEV provoked an increase in ALT, elevation of anti-HEV IgG, and slight lymphatic infiltration or necrotic change in the liver, although obvious clinical symptoms were not observed [1,20]. Furthermore, cynomolgus monkeys infected with HEV by the oral route did not show any clinical and hematological changes associated with acute hepatitis or HEV infection [12].…”
Section: Discussionmentioning
confidence: 95%